Gadd45β expression in chondrosarcoma: A pilot study for diagnostic and biological implications in histological grading - Ishido Yasuhiro; Yamamoto Takuya; Nagano Satoshi; Yokouchi Masahiro; Sakakima Harutoshi; Tanimoto Akihide; Zenmyo Michihisa; Komiya Setsuro; Ijiri Kosei (BMC, 2010)
Abstract Background Although the diagnosis of chondrosarcoma, especially the distinction between enchondroma and low-grade chondrosarcoma or low-grade chondrosarcoma and high-grade chondrosarcoma, is pathologically difficult, differential diagnosis is very important because the treatment strategies for these diseases are completely different. The grading system is crucial in predicting biologic behavior and prognosis, however, exact pathological grading is difficult using only routine examinations because the criteria of the grading system are not necessarily definitive. Growth arrest and DNA damage-inducible protein 45β (GADD45β) is an essential molecule for chondrocytes during terminal differentiation. In the present study, we investigated the immunohistochemical expression of GADD45β in enchondroma, and chondrosarcoma of histological grades I, II, and III, to clarify the diagnostic significance of GADD45β in pathological grading of chondrosarcoma. Methods Twenty samples (enchondroma = 6, chondrosarcoma grade I = 7, grade II = 6, grade III = 1) were used for immunohistochemical analysis to investigate the expression of GADD45β. Quantitative analysis was performed to compare the number of GADD45β positive cells and pathological grading. Results Over 70% of the cells in enchondromas expressed GADD45β. On the other hand, the expression of GADD45β decreased significantly according to the histological grade of chondrosarcoma (grade I: 45%; grade II: 13.8%; and grade III: 3.8%). Conclusions The association of GADD45β expression and pathological grading of chondrosarcoma in the present study suggests that the immunohistochemical study of GADD45β may be a specific diagnostic parameter for chondrosarcoma cell differentiation.